Procedural Justice, Legitimacy, and School Principals’ Evaluations of School Resource Officers: Support, Perceived Effectiveness, Trust, and Satisfaction - Wolfe, Scott E. (Criminal justice policy review, 2017)
Violence and active shooter situations in schools have been important issues to the public, policy makers, and scholars in recent years. School resource officers (SROs) are widely used in efforts to address school crime-related threats. Yet, little is known about the factors that influence key stakeholders’ (e.g., school principals) evaluations of such officers. The present study uses survey data from a sample of public school principals in South Carolina to examine the role of procedural justice theory in understanding evaluations of SROs. The results reveal that procedural justice is associated with principals’ support for SROs, perceived effectiveness of SROs, and level of trust and satisfaction in SROs. The policy implications of the results center on the importance of SRO procedural fairness in maintaining quality relationships with top school administrators which may ultimately have a wider impact on the success of SRO programs.